Frameworks for generalisation of flexible behaviour: insights from mouse behaviour and neural computation - Samborska, V (2023)
It would be a daunting task to learn everything from scratch each time we are faced with a new problem. Instead, humans and other animals are helped by the fact that few situations in life are truly novel. Thus, we can draw upon previous experiences of similar situations and come up with our ‘best guess’ of how to deal with a new task at hand. In this thesis, I will attempt to answer the question of how this ability to generalise knowledge between different situations might be achieved in the brain.